2014
DOI: 10.1007/s00417-014-2853-6
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of oxidative stress levels in the conjunctival epithelium of patients with or without dry eye, and dry eye patients treated with preservative-free hyaluronic acid 0.15 % and vitamin B12 eye drops

Abstract: These findings indicate that oxidative stress is associated with dry eye and that hyaluronic acid/vitamin B12 eye drops may attenuate oxidative stress and inflammation, improving dry eye symptoms. Further study in controlled clinical trials is warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
57
0
10

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(67 citation statements)
references
References 32 publications
0
57
0
10
Order By: Relevance
“…Dry eye disease has been shown to result in reduction in corneal thickness [55] and irregularities in corneal surface [56] which can ultimately lead to impaired visual acuity [57, 58]. Dry eye disease has also been reported to increase oxidative stress in conjunctival epithelium [59] which could contribute to the aforementioned oxidative stress pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Dry eye disease has been shown to result in reduction in corneal thickness [55] and irregularities in corneal surface [56] which can ultimately lead to impaired visual acuity [57, 58]. Dry eye disease has also been reported to increase oxidative stress in conjunctival epithelium [59] which could contribute to the aforementioned oxidative stress pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Limitation of this study includes small sample size and short duration of follow-up and failure to follow-up with dry eye signs and symptoms. Moreover, due to the design of the study, it is not possible to determine whether the benefit of reduction in oxidative stress continues to persist after cessation of treatment (Macri et al 2015). In addition, the authors have failed to demonstrate that topical concentrations of vitamin B12 would indeed have an effect on ocular tissue when used at the frequency of the study.…”
Section: Intervention Studies In Humansmentioning
confidence: 99%
“…HA eye drops may be promoting OS tissue healing by humidifying the OS, thus bringing back the integrity of corneal and conjunctival epithelium. It has been shown that topically applied HA stimulates wound healing in an animal model25 and attenuates oxidative stress and inflammation, thus improving dry eye symptoms 26…”
Section: Discussionmentioning
confidence: 99%